Adaptasi Digital Perbankan dalam Memenuhi Preferensi Generasi Z di Era Digital : Sebuah Systematic Literature Review Berbasis Technology Acceptance Model (TAM) - Prawira, Anggun Wida; Riyadi, Slamet (Universitas Hamzanwadi, 2025)
The digital transformation in the banking sector has emerged as a critical global phenomenon, particularly in addressing the evolving needs of Generation Z—a cohort raised in a digitally connected environment. This study aims to assess the extent to which banking institutions, both in Indonesia and globally, have adapted to the digital expectations of Gen Z. Employing a Systematic Literature Review (SLR) approach, this research analyzes 21 peer-reviewed articles sourced from Scopus, ScienceDirect, and Google Scholar, published between 2019 and 2025. The findings identify key determinants influencing Gen Z’s adoption of digital banking, including perceived ease of use, data security, user experience (UX/UI), and service personalization. Results suggest that digital banks and neobanks are more appealing to Gen Z than traditional financial institutions. The study recommends strengthening technology-driven innovation, implementing customer-centric approaches, and fostering strategic collaboration with fintech companies. Managerial implications highlight the need for technology-based service development, enhancement of digital financial literacy, and the expansion of inclusive and sustainable financial ecosystems